OPTIMIZATION OF THE LEARNING PROCESS BY AUTOMATION OF OBTAINING THE SCHEDULE BASED ON TELEGRAM - Vadim A. Chernov; Dinar R. Fatikhov; Azat D. Ramazanov; Gulnara A. Gareeva (International Journal of Advanced Studies, 2023)
This article describes the process of creating a Telegram bot that would automatically send class schedules for full-time/part-time students on a daily basis. A feature of Telegram bots is - simplicity of use and minimization of resources, which greatly simplifies its creation and interaction with it.